Le texte syriaque de la ṭablītō éthiopienne : une réponse aux remarques du Pr. Dr. Michael Waltisberg - Desreumaux, Alain (Aethiopica, 2022)
We thank Prof. Dr Waltisberg for his correction of vocalization and for his grammatical contribution. He confirms the unusual form of the verb in the formula and the meaning of bad as a shortcut of which he lists many examples. We take this opportunity to add three Maronite ṭablyōtō found in Lebanon.